Rekonstruksionisme Pendidikan Islam Menurut Muhammad Iqbal - Herlini Puspika Sari (AL-FIKRA, 2020)
Education should spearhead and reform or reconstruct communities so that they become better. Islamic education must be directed to the fulfillment of philosophical ideals (self strength) so that it has a faith-based self quality. The education of the modern world must be able to integrate all the elements of values that exist in life, have worldly and finality aspects so that in their development these two aspects are equally running and can create an accountable education. This is an explorative descriptive qualitative research that describes philosophical views and thoughts about the reconstruction of Islamic education according to Muhammad Iqbal. The Finding this research Muhammad Iqbal views that now is the time for Muslims to reconstruct their thinking in various fields, including the field of Islamic education which aims to form human beings (real people) with human criteria that have strength, broad insight, fair deeds and have wise policies so that being a human being in the Qur'an is mentioned as a perfect being.